PEMBELAJARAN MENULIS TEKS CERITA PENDEK DENGAN MENGGUNAKAN METODE INKUIRI BERBANTUAN MEDIA GAMBAR PADA SISWA KELAS XI SMA PLUS TAUHIDUL AFKAR CIANJUR - Resi Nopsrianti Rostiawan; Rochmat Tri Sudrajat; Yusef Ahmad F. (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims, 1) how the scenario and implementation of learning to write short story texts using the inquiry method assisted by image media in class XI IPA SMA Plus Tauhidul Afkar, 2) how teachers and students respond to learning to write short story texts using assisted inquiry method image media? 3) What are the difficulties experienced by class XI students of SMA Plus Tauhidul Afkar in completing short story writing tasks? Researchers for their awareness use descriptive methods. The data collection techniques are observation, documentary, interview, test, and questionnaire. Data collection was carried out by researchers, namely observation guideline sheets, recording devices, interview guideline sheets, test sheets, student activity observation sheets, and questionnaire sheets. Based on the results of data analysis on the implementation, it can be concluded that the planning and implementation of inquiry learning in writing short stories in class XI IPA for SMA Plus Tauhidul Afkar students are synchronized with the 2013 curriculum. The results obtained by students on learning to write short stories using the inquiry method are successful and can increase creativity.